HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KEPERCAYAAN DIRI SISWA - Suryadi, Putu Maya Ratih; Manangkot, Meril Valentine; Kamayani, Made Oka Ari; Yanti, Ni Putu Emy Darma (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p08, 2023)
Self-confidence is an attitude of belief in one's own abilities seeing about to achieve something. Self-confidence is a key for everyone to promote the performance, specifically the adolescents. Adolescents are prone to having low self-confidence since they are more unstable to their feelings. They are prone to have insecurities while regarding something on social media. The intensity of using social media, thus can affect the confidence of its users. This research aims at determining the relationship between the intensity of social media use and self-confidence on the students at SMA Kristen Harapan Denpasar. This research used the correlative descriptive study with the quantitative method with a cross sectional approach. The sampling uses a simple random and stratified sampling techniques from the 154 students in class XII in the Science and Social science as the respondents. Data collection uses the questionnaire spread to respondents via google form had tested as the valid and reliable survey to measure the variable of the data. The analysis test used was a Spearman Rank correlation test with a 95% confidence level. The results shows that there was a fairly close relationship in the direction of a negative relationship between the intensity of social media use and confidence (p < 0,001, r = - 0,430). It can be deduced that when using social media too intense can give the impacts to adolescent’s self-confidence. It means that the higher of the intensity in using social media then the lower of self-confidence possessed by the adolescents, and vice versa. An adolescent is expected to use social media well and wisely to avoid the prospect of a lower self-confidence.